صعوبات التنظيم الانفعالي وعلاقته بالطموح الأكاديمي لدى عينة من الطلبة المراهقين في التعليم الثانوي العام (Journal of Hama University, 2024)
The aim of the current research is to identify the level of difficulties in emotional regulation and the level of academic ambition among members of the research sample of adolescent students in secondary education. And studying the correlation between difficulties in emotional regulation and academic ambition among members of the research sample. And revealing the differences between the average scores of the research sample’s answers on the Difficulties in Emotional Regulation Scale and the Academic Ambition Scale according to the two research variables: (gender, academic specialization). The research relied on the descriptive analytical method. The researcher used the Difficulties in Emotion Regulation Scale (DERS), which consists of (36) items. She used the Academic Ambition Scale prepared by Snyder et al. (1991), which consists of (12) items. The sample included The research included (245) male and female students from the third year of general secondary school, male and female, in Damascus Governorate’s official secondary schools (literary and scientific). Among the most important results of the research: There is a negative and significant correlation in the answers of the research sample members between the difficulties of emotional regulation and academic ambition among the research sample members. There are statistically significant differences between the average scores of the research sample’s answers on the scale of difficulties in emotional regulation according to the gender variable in favor of female students. There are no statistically significant differences between the average scores of the research sample’s answers on the scale of difficulties in emotional regulation according to the academic specialization variable. There are no statistically significant differences between the average scores of the research sample’s answers on the academic ambition scale according to the gender variable. There are statistically significant differences between the average scores of the research sample’s answers on the academic ambition scale according to the academic specialization variable in favor of scientific specialization.